Effects of Myopia on Rates of Change in Optical Coherence Tomography Measured Retinal Layer Thicknesses in People with Multiple Sclerosis and Healthy Controls. (4th March 2023) - Kalaitzidis, Grigorios; Pellegrini, Nicole; Nagy, Natalia; Vasileiou, Eleni; Ehrhardt, Henrik; Reppen, Abbey; Murphy, Olwen C.; Moussa, Hussein; Filippatou, Angeliki; Lambe, Jeffrey; DuVal, Anna; Fioravante, Nicholas; et al.
Abstract: Purpose: To quantify the associations of myopia with longitudinal changes in retinal layer thicknesses in people with multiple sclerosis (PwMS) and healthy controls (HC). Methods: A cohort of PwMS and HC with recorded refractive error (RE) prospectively scanned on Cirrus HD-OCT at the Johns Hopkins MS Center was assessed for inclusion. Exclusion criteria included OCT follow-up < 6 months, ocular comorbidities, incidental OCT pathologies, and inadequate scan quality. Eyes were classified as having high myopia (HM) (RE≤ −6 diopters), low myopia (LM) (RE> −6 and ≤ −3 diopters), or no myopia (NM) (RE> −3 and ≤ +2.75). Linear mixed-effects regression models were used in analyses. Results: A total of 213 PwMS (eyes: 67 HM, 98 LM, 207 NM) and 80 HC (eyes: 26 HM, 37 LM, 93 NM) were included. Baseline average ganglion cell/inner plexiform (GCIPL) and peri-papillary retinal nerve fiber layer (pRNFL) thicknesses were lower in MS HM compared with MS NM (diff: −3.2 µm, 95% CI: −5.5 to −0.8, p  = 0.008 and −5.3 µm, 95% CI: −9.0 to −1.7, p  = 0.004, respectively), and similarly in HC HM, as compared with HC NM. Baseline superior, inferior, and nasal pRNFL thicknesses were lower in HM compared with NM, while temporal pRNFL thickness was higher, both in MS and HC (MS: 7.1 µm, 95% CI: 2.7–11.6, p  = 0.002; HC: 4.7 µm, 95% CI: −0.3 to 9.7, p  = 0.07). No longitudinal differences in rates of GCIPL change were noted between HM and LM vs. NM, either in MS or HC. Conclusion: Cross-sectional differences in average GCIPL and pRNFL thicknesses are commonly seen in people with HM as compared to reference normative values from people with NM and can lead to false attribution of pathology if RE is not taken into account. However, our study suggests that longitudinal changes in average GCIPL thickness in PwMS with myopia are similar in magnitude to PwMS with NM, and therefore are appropriate for monitoring disease-related pathology.